Risk-based approach to choosing the production asset management strategy for energy company - V. M. Levin; N. P. Guzhov; D. A. Boyarova (Известия высших учебных заведений: Проблемы энергетики)
RELEVANCE: The possibility of a reasonable choice of an alternative strategy for the organization of maintenance and repair (M&R) of the power company's equipment is a guarantee of the successful implementation of its strategic priorities. The tasks in this direction are quite relevant.PURPOSE: To develop a unified methodology that, from the general standpoint of a risk-based approach, would allow comparing two alternative strategies for managing the assets of an energy company "by periodicity, operating time" and "by technical condition", according to a set of key criteria for the effectiveness of M&R.METHODS: When solving problems, methods of forming and adjusting schedules for repairs of electrical equipment, calculating reliability and probabilities of failure in the power supply system of consumers, taking into account its circuit features, assessing the technical condition of equipment according to non-destructive testing and diagnostics, comparing the costs of maintaining and restoring reliability and damages from its violations were used.RESULTS: A risk-oriented methodology has been developed and verified, which makes it possible to evaluate and select the optimal equipment maintenance strategy for the energy company according to uniform efficiency criteria. An algorithmic implementation of the developed methodology is obtained, which is the basis of a computing complex for choosing and making decisions. The verification of the methodology and algorithm is carried out on the example of a real object – a power supply system for oil production consumers using reliable operational and diagnostic information.CONCLUSION: The results obtained fully compensate for the lack of methodological possibilities in comparing two basic alternative strategies for electrical equipment maintenance based on a single risk-based approach. The developed methodology is a unified decision-making tool at the stage of alternative analysis. The illustration of the methodology by a real numerical example demonstrates the consistency of the solutions obtained with the results of expert assessments and operational experience.